A novel berberine‐metformin hybrid compound exerts therapeutic effects on obese type 2 diabetic rats. (21st April 2019) - Jia, Dan; Li, Zi Wen; Zhou, Xinxin; Gao, Ying; Feng, Yifan; Ma, Min; Wu, Zhengzhi; Li, Weimin
Summary: In this study, we investigated the biological activities of a novel berberine‐metformin hybrid compound (BMH473) as an anti‐diabetic agent. BMH473 exhibited significant anti‐hyperglycaemic and anti‐hyperlipidaemic effects on T2DM rats. In white adipose tissue, BMH473 reduced the perirenal and epididymal adipose tissue mass and modulated the lesions in perirenal adipose tissue, by inhibiting the protein expressions of PPAR‐Ɣ, C/EBP‐α and SREBP‐1c as well as the mRNA expressions of lipogenic genes. Moreover, BMH473 downregulated the levels of pro‐inflammatory cytokines in perirenal adipose tissue through the suppression of p‐NF‐κB. In liver, BMH473 reduced liver ectopic fat accumulation, by regulating the protein expression levels of SREBP‐1c and PPAR‐α as well as the mRNA expression levels of lipogenic genes. In addition, BMH473 inhibited hepatic gluconeogenesis by promoting the phosphorylation levels of AMPK α and ACC, and down‐regulating the mRNA expression levels of FBPase, G6Pase and PEPCK . Furthermore, BMH473 exhibited significant inhibitory effects on lipogenesis and lipid accumulation in 3T3‐L1 adipocytes by modulating the protein expression levels of PPAR‐Ɣ, C/EBP‐α and SREBP‐1 c as well as the mRNA expression levels of lipogenic genes. In conclusion, our results suggest that the newly synthesized BMH473 is beneficial for maintaining glucose and lipid homeostasis in type 2 diabetic rats, and exhibits better anti‐hyperlipidaemic effects compared to metformin and berberine.